The Effect of Hypnobreastfeeding and Endorphin Massage on Breastfeeding Anxiety in Post Partum Mothers at Midwife's Independent Practice Place Palembang City in 2024 - Humairoh, Khairunnisa Humairoh; Martini, Sri; Suprida, Suprida (Journal of Maternal and Child Health Sciences (JMCHS), 2024)
Backgorund: One of the factors in the failure of themother's breastfeeding process is anxiety in the PostPartum mother. Anxiety when breastfeeding will inhibitthe letdown reflex so that breast milk production isreduced. Efforts to reduce anxiety levels can be done withHypnobreastfeeding and endorphin massage. Purpose: Todetermine the effect of Hypnobreastfeeding andEndorphin Massage on Breastfeeding Anxiety in PostPartum Mothers at TPMB Palembang City in 2024.Methode: This type of research is pre-experimental andhas a two group pretest and posttest design. The sample inthe study was 32 respondents using a purposive samplingtechnique. Data collection used the HARS instrument anddata analysis used Wilcoxon. The Results : Based on thetest, a p-value of 0.000 was obtained (p-value <0.05),meaning that there was an effect of providingHypnobreastfeeding and Endorphin Massageinterventions on breastfeeding anxiety in Post Partummothers. Conclusions: There is an effect of providingHypnobreastfeeding and Endorphin Maasgaeinterventions on breastfeeding anxiety in Post Partummothers at TPMB Palembang City in 2024.